Rekonstruksi Kewenangan Dpd Dalam Sistem Bikameral Lunak Indonesia: Memperkuat Representasi Daerah - Deizan Azriel Drahmasyfa; Laila Nur Fadila; Anaku Alana; Muhammad Renaldi Jaelani (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2025)
Indonesia’s soft bicameral system places the Regional Representative Council in a functionally weak position compared to the House of Representatives, limiting territorial representation. This normative-legal study analyzes legislation, constitutional doctrine, and comparative bicameral systems to reconstruct the DPD’s powers without altering the presidential principle. Historically, the DPD emerged from a political compromise between decentralization demands and efforts to preserve DPR supremacy. Constitutionally, restrictions in Article 22D of the 1945 Constitution create a subordinated status at odds with territorial representation. Recommended reconstruction includes strengthening sectoral legislative rights, substantive oversight over central policies affecting regions, and binding consultative rights on fiscal policy and regional autonomy. These measures are expected to enhance the DPD’s political legitimacy, promote distributive justice among regions, and improve the constitutional system’s adaptability to complex center–region relations under broad autonomy. The study concludes that, without constitutional empowerment and internal institutional reform, Indonesia’s bicameralism will remain asymmetric and symbolic; therefore limited constitutional amendment and internal reform are necessary for the DPD to act as a genuine co-legislator on regional sectoral matters.